QSAR Study of Indolylisoxazoline Analogues for Their Antiprostat Activity - Jafar La Kilo; Akram La Kilo (Universitas Negeri Gorontalo, 2019)
ABSTRACT Quantitative Structure-Activity relationship study of 13 Indolylisoxazoline analogues as antiprostat agent using multiple linear regression (MLR) has been done. Geometri optimization of Indolylisoxazoline analogues using molecular mechanics (MM+) method. The best QSAR model from regression analysis is log IC50 Pred = 30,877 - 71,847 x qC10 + 165,070 x qC11 + 70,106 x qC13 with most influents descriptor to antiprostat activity are qC10, qC11 dan qC13.